1989
DOI: 10.1136/ard.48.7.542
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine sulphate in the treatment of rheumatoid arthritis: a double blind comparison of two dose regimens.

Abstract: SUMMARY A controlled, double blind, parallel group, long term study of hydroxychloroquine sulphate in the treatment of rheumatoid arthritis, comparing daily doses of 200 mg and 400 mg, is described. The trial involved 54 patients with moderate disease activity who had not previously received antimalarial drugs. Forty three patients completed the one year treatment. The groups receiving different doses were homogeneous and did not differ in any of the 25 monitored indicators. Both dose regimens were effective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…CQ in combination with the immunosuppressants, dehydro-epiandrosterone and 2-chloro-2 0 -deoxyadenosine, showed additivity in suppressing PHA stimulation, in contrast to combinations of some other immunosuppressants which showed synergistic inhibition (Klinefelter and Achurra 1973). Other studies confirmed the effects of CQ 3 lM on PHA-stimulated tritiated thymidine or deoxyuridine incorporation using salicylate 1 mM (a known inhibitor of lymphocyte proliferation) as a reference standard (Pavelka et al 1989). In view of the latter observation, the earlier comparison by Panayi and co-workers of the effects of treatment with CQ with aspirin and aspirin alone may require revision on the basis of interpreting the potential effects of salicylate from ingested aspirin alone in diminishing lymphocyte proliferation in patients with RA Panayi et al 1973).…”
Section: Cellular Immune Reactionsmentioning
confidence: 71%
See 1 more Smart Citation
“…CQ in combination with the immunosuppressants, dehydro-epiandrosterone and 2-chloro-2 0 -deoxyadenosine, showed additivity in suppressing PHA stimulation, in contrast to combinations of some other immunosuppressants which showed synergistic inhibition (Klinefelter and Achurra 1973). Other studies confirmed the effects of CQ 3 lM on PHA-stimulated tritiated thymidine or deoxyuridine incorporation using salicylate 1 mM (a known inhibitor of lymphocyte proliferation) as a reference standard (Pavelka et al 1989). In view of the latter observation, the earlier comparison by Panayi and co-workers of the effects of treatment with CQ with aspirin and aspirin alone may require revision on the basis of interpreting the potential effects of salicylate from ingested aspirin alone in diminishing lymphocyte proliferation in patients with RA Panayi et al 1973).…”
Section: Cellular Immune Reactionsmentioning
confidence: 71%
“…Treatment of RA patients with HCQ (200-400 mg/day) for relatively long periods of time (months/years) has been found to reduce those biomarkers that are regulated by the cytokines IL-1 and IL-6, namely ESR and plasma levels of acute phase reactants and haptoglobin, coincident with improvement of physical signs and disease symptoms (Klinefelter and Achurra 1973;Dixon et al 1981;Pavelka et al 1989). Furthermore, plasma IgG concentrations were increased while the IgM decreased after 1 year's treatment with HCQ 200 or 400 mg/day (Kalmanson and Guze 1963).…”
Section: Actions On the Immune System And Cytokinesmentioning
confidence: 98%
“…Additionally, hydroxychloroquine ( 1 , HCQ) is an effective non-steroidal drug with anti-inflammatory activity for the treatment of rheumatoid arthritis (RA) in patients with cardiovascular disease [ 7 9 ]. The World Health Organization has identified HCQ ( 1 ) as an essential antimalarial medication for a basic healthcare system, but global access to HCQ ( 1 ) has been hindered by high manufacturing costs of the API.…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of MTX in the treatment of RA has been demonstrated in observational studies and randomized controlled trials, and established over the long term [7]. Other conventional synthetic DMARDs (csDMARDs), including hydroxychloroquine [8], sulfasalazine [9], and leflunamide [10] have also been successfully used in RA patients and remain important therapies [5]. However, because MTX is the most extensively studied drug it is usually used as a first line unless contraindicated [6].…”
Section: Introductionmentioning
confidence: 99%